2022
DOI: 10.1177/01634437221111923
|View full text |Cite
|
Sign up to set email alerts
|

Platform governance at the margins: Social media creators’ experiences with algorithmic (in)visibility

Abstract: While champions of the “new” creative economy consistently hype the career possibilities furnished by YouTube, Instagram, TikTok, and the like, critics have cast a spotlight on the less auspicious elements of platform-dependent creative labor: exploitation, insecurity, and a culture of overwork. Social media creators are, moreover, beholden to the vagaries of platforms’ “inscrutable” socio-technical systems, particularly the algorithms that enable (or – conversely – thwart) their visibility. This article draws… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 48 publications
(65 reference statements)
2
59
0
1
Order By: Relevance
“…A recurring theme in users’ experiences of de-platforming is the loss of income and work opportunities arising from the deletion of their profile and content and from platforms’ opaque moderation in general. Consistent with previous research on the creator economy (Bishop, 2019; Duffy, 2020; Duffy & Meisner, 2022; Glatt, 2022), participants reported that being tied to platforms’ whims resulted in work instability and precarity, forcing them to rely on the “algorithmic boss” (Duffy, 2020, p. 103) and with many reporting significant financial losses as some of the most crippling and challenging effects of de-platforming. Some went as far as claiming to have lost thousands in earnings in the aftermath of their accounts’ deletions:[M]y photography work went from several thousand a month to near zero.…”
Section: “It Has Destroyed My Income”: Censorship’s Economic and Prof...supporting
confidence: 73%
See 3 more Smart Citations
“…A recurring theme in users’ experiences of de-platforming is the loss of income and work opportunities arising from the deletion of their profile and content and from platforms’ opaque moderation in general. Consistent with previous research on the creator economy (Bishop, 2019; Duffy, 2020; Duffy & Meisner, 2022; Glatt, 2022), participants reported that being tied to platforms’ whims resulted in work instability and precarity, forcing them to rely on the “algorithmic boss” (Duffy, 2020, p. 103) and with many reporting significant financial losses as some of the most crippling and challenging effects of de-platforming. Some went as far as claiming to have lost thousands in earnings in the aftermath of their accounts’ deletions:[M]y photography work went from several thousand a month to near zero.…”
Section: “It Has Destroyed My Income”: Censorship’s Economic and Prof...supporting
confidence: 73%
“…Brands or workplaces that seek out content creators and influencers also use a large following as a proxy measure of success (García-Rapp, 2017; Glatt, 2022). This inevitably means that creators’ success is almost synonymous with visibility (Duffy & Meisner, 2022) and relies upon metrics such as views and following (Banet-Weiser, 2018). As such, losing profiles built through years of digital labor to then have to start again is a severe reputational blow that, according to participants, has cost them work and opportunities.…”
Section: “It’s Affecting My Relevance”: the Reputational Impact Of De...mentioning
confidence: 99%
See 2 more Smart Citations
“…A central issue is social media algorithms that increase duration and intensity of exposure in ways that can be opaque to users 5. Neither in government statements nor elsewhere are there specific suggestions about what limits should be set on these quantitative aspects of social media viewing.…”
mentioning
confidence: 99%